Discourse on Adolescent Deviant Behavior on Social Media Facebook: Indonesian Youth Group Caption - Novita, Ely; Warsono, Warsono; Wisnu, Wisnu (Universitas Malikussaleh, 2020)
This study aims to determine the content or discourse of deviant behavior by teenagers on Facebook social media and to find out which vocabulary is most widely used by Indonesian teenage grub caption members. This type of research is qualitative with content analysis methods. The subjects of this study were members of the Indonesian Youth Caption group, while the informants used the internet. Based on the results of the analysis and discussion of the data, it shows that the discourse on deviant behavior by teenagers in the Facebook Social Media Grub is: (1) Sharing pornographic videos in the form of adult films or real videos of teenagers who commit deviations, out of habit, and follow what other grub members do, (2) Share pornographic links that can be accessed by members via YouTube or WhatsApp and vent things they cannot do in their daily life, (3) Share pornographic photos for entertainment, are influenced by uploads fellow members, get audience and attention. Then the vocabulary that is often used by teenagers on the Facebook Social Media Grub, namely: (1) Sange, a sentence for men who already understand the adult world, is often used in everyday life, especially teenage boys, slang, and words. which leads to negative and dirty things, (2) Whatsapp media is used to get videos that are is viral, (3) Chat for women because they are used to seeing uploads made by young women, are interested, and feel bored with male friendships.